Pectic polysaccharide from Nelumbo nucifera leaves promotes intestinal antioxidant defense in vitro and in vivo. Issue 21 (7th October 2021) - Huang, Chao; Peng, Xi; Pang, De-Jiang; Li, Juan; Paulsen, Berit Smestad; Rise, Frode; Chen, Yu-Long; Chen, Zheng-Li; Jia, Ren-Yong; Li, Li-Xia; Song, Xu; Feng, Bin; et al.
Abstract : A pectic polysaccharide NNLP-I-I from lotus leaves exhibited antioxidant property through regulating Nrf2-mediated intestinal antioxidant defense system, which will be valuable for its further applications on the treatments of intestinal diseases. Abstract : In this study, the Nelumbo nucifera leaf polysaccharide (NNLP) was isolated by hot water extraction and ethanol precipitation. DEAE anion exchange chromatography and gel filtration were further performed to obtained the purified fraction NNLP-I-I, the molecular weight of which was 16.4 kDa. The monosaccharide composition analysis and linkage units determination showed that the fraction NNLP-I-I was a pectic polysaccharide. In addition, the NMR spectra analysis revealed that NNLP-I-I mainly consisted of a homogalacturonan backbone and rhamnogalacturonan I, containing a long HG region and short RG-I region, with AG-II and 1–3 linked rhamnose as side chains. The biological studies demonstrated that NNLP-I-I displayed antioxidant properties through mediating the Nrf2-regulated intestinal cellular antioxidant defense, which could protect cultured intestinal cells from oxidative stress and improve the intestinal function of aged mice.